A comparative study between Machen and McIntire concerning their view of the church as related to their influence on the Presbyterian Church in Korea - Hofmeyr, J.W. (Johannes Wynand), 1947- (University of Pretoria, 2013)
Thesis (PhD (Church History))--University of Pretoria, 2007.